The Afterlife of John Brown - Herrington, E.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2005)
"An examination of the influence--however contested--of John Brown of the Harper's Ferry Rebellion on the national narrative of the United States"--Amazon.com.
Keywords: United States—History.; History, Modern; America—History.; US History; Modern History; History of the Americas